2013
DOI: 10.1002/bjs.9335
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of abdominal surgical emergencies in infants and children

Abstract: Knowledge of abdominal disorders in childhood, their specific presentation, diagnosis and treatment facilitates management of children with acute abdomen in emergency departments. Imaging and minimally invasive techniques are becoming increasingly important in the diagnosis of acute abdomen in children. Urgent operation remains the cornerstone of therapy for most acute abdominal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 67 publications
(74 reference statements)
1
12
1
2
Order By: Relevance
“…Our findings showed that when the aetiology of surgical abdomen was matched with age groups and gender of our patients, the relative frequency of the various causes was consistent with earlier reports was obtained [1][2][3][7][8][9][10][11] . Patients below five years were excluded from the study as most of them were referred directly to the specialist paediatrics surgery unit where better ancillary support [intensive care unit and paediatrics anaesthetists] services were available.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings showed that when the aetiology of surgical abdomen was matched with age groups and gender of our patients, the relative frequency of the various causes was consistent with earlier reports was obtained [1][2][3][7][8][9][10][11] . Patients below five years were excluded from the study as most of them were referred directly to the specialist paediatrics surgery unit where better ancillary support [intensive care unit and paediatrics anaesthetists] services were available.…”
Section: Discussionsupporting
confidence: 92%
“…Pain is the predominant symptom in patients with acute abdomen. The aetiology of this acute abdominal emergency is numerous and includes traumatic, infectious and inflammatory conditions 1 . Of importance is the need for a quick decision on whether it is a surgical abdomen (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Takehara and coworkers had one salpingo-oophorectomy in 15 patients with irreducible ovary and Boley and co-workers report four non-viable ovaries in another group of 15 patients (16,17). In view of these results and our own findings we consider an irreducible ovary an indication for emergency surgery in contradiction to a newly published recommendation by van Heurn and co-workers (18).…”
Section: Accepted Manuscriptcontrasting
confidence: 71%
“…2 The diagnosis of appendicitis can be difficult in children because its symptoms vary widely, and a delay in its diagnosis is associated with increased morbidity and mortality. 8 Thus, it is necessary to use more laboratory tests and imaging methods in patients with suspected acute appendicitis. 9 In our hospital, the percent of misdiagnosis was about 9%.…”
Section: Discussionmentioning
confidence: 99%